PENGEMBANGAN E-COMMERCE USAHA KECIL MENENGAH KAMPUNG BATIK BETUNGAN BERBASIS WEB - Hafizh, Habib Al; Aspriyono, Hari; Akbar, Abdussalam Al (Jurnal TAM (Technology Acceptance Model), 2024)
E-commerce is a website-based online sales platform. This e-commerce is a program built with the PHP programming language and MySQL as a database processor. This research was conducted at UKM (Small and Medium Enterprises) Kampung Batik Betungan. E-commerce UKM Kampung Batik Betungan aims to introduce and make sales online. This e-commerce contains products produced by UKM Kampung Batik Betungan. E-commerce UKM Kampung Batik Betungan has been tested to 20 people as correspondents at UKM Kampung Batik Betungan and the community around UKM. Correspondents are batik craftsmen and the community in the environment of UKM Kampung Batik Betungan. From the test, the answers obtained based on the results of system testing conducted at UKM Kampung Batik Betungan stated 80.84% very good and 19.16% stated good to the system that has been made. So from the presentation results obtained, e-commerce UKM Kampung Batik Betungan can be used as an online sales platform.